Conductive panel cooling by using coupled effects of nano-jet impingement, double rotating cylinders and magnetic field under cross-flow - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Emerald Group Publishing Ltd, 2024)
PurposeThis study aims to examine the effects of cross-flow and multiple jet impingement on conductive panel cooling performance when subjected to uniform magnetic field effects. The cooling system has double rotating cylinders.Design/methodology/approachCross-flow ratios (CFR) ranging from 0.1 to 1, magnetic field strength (Ha) ranging from 0 to 50 and cylinder rotation speed (Rew) ranging from -5,000 to 5,000 are the relevant parameters that are included in the numerical analysis. Finite element method is used as solution technique. Radial basis networks are used for the prediction of average Nusselt number (Nu), average surface temperature of the panel and temperature uniformity effects when varying the impacts of cross-flow, magnetic field and rotations of the double cylinder in the cooling channel.FindingsThe effect of CFR on cooling efficiency and temperature uniformity is favorable. By raising the CFR to the highest value under the magnetic field, the average Nu can rise by up to 18.6%, while the temperature drop and temperature difference are obtained as 1.87 degrees C and 3.72 degrees C. Without cylinders, magnetic field improves the cooling performance, while average Nu increases to 4.5% and 8.8% at CR = 0.1 and CR = 1, respectively. When the magnetic field is the strongest with cylinders in channel at CFR = 1, temperature difference (Delta T) is obtained as 2.5 degrees C. The rotational impacts on thermal performance are more significant when the cross-flow effects are weak (CFR = 0.1) compared to when they are substantial (CFR = 1). Cases without a cylinder have the worst performance for both weak and severe cross-flow effects, whereas using two rotating cylinders increases cooling performance and temperature uniformity for the conductive panel. The average surface temperature lowers by 1.2 degrees C at CFR = 0.1 and 0.5 degrees C at CFR = 1 when the worst and best situations are compared.Originality/valueThe outcomes are relevant in the design and optimization-based studies for electric cooling, photo-voltaic cooling and battery thermal management.
Keywords: Cross flow; Rotating cylinder; Nanofluid; Magnetic field; Finite element method; Radial basis function